2023
DOI: 10.3389/fimmu.2023.1290762
|View full text |Cite
|
Sign up to set email alerts
|

Current status and future challenges of CAR-T cell therapy for osteosarcoma

Shizhe Li,
He Zhang,
Guanning Shang

Abstract: Osteosarcoma, the most common bone malignancy in children and adolescents, poses considerable challenges in terms of prognosis, especially for patients with metastatic or recurrent disease. While surgical intervention and adjuvant chemotherapy have improved survival rates, limitations such as impractical tumor removal or chemotherapy resistance hinder the treatment outcomes. Chimeric antigen receptor (CAR)-T cell therapy, an innovative immunotherapy approach that involves targeting tumor antigens and releasing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 137 publications
0
0
0
1
Order By: Relevance
“…Here, we have found that the Akt-mTOR signaling pathway was involved in the inhibitory effect of PRKCI on osteosarcoma in vitro . Despite the fact that surgical resection combined with adjuvant therapies, including chemotherapy, can significantly improve the prognosis of primary osteosarcoma, which achieves a 5-year survival rate of approximately 70%, the overall survival rate for recurrent or metastatic osteosarcoma drops dramatically to around 25% due to factors such as chemotherapy resistance and surgical limitations ( 47 ). Our current research elucidated the interaction between PRKCI and SQSTM1, demonstrating that PRKCI upregulated SQSTM1 and mediated critical functions in the proliferation and progression of osteosarcoma cells through the activation of the Akt/mTOR signaling pathway.…”
Section: Discussionmentioning
confidence: 99%
“…Here, we have found that the Akt-mTOR signaling pathway was involved in the inhibitory effect of PRKCI on osteosarcoma in vitro . Despite the fact that surgical resection combined with adjuvant therapies, including chemotherapy, can significantly improve the prognosis of primary osteosarcoma, which achieves a 5-year survival rate of approximately 70%, the overall survival rate for recurrent or metastatic osteosarcoma drops dramatically to around 25% due to factors such as chemotherapy resistance and surgical limitations ( 47 ). Our current research elucidated the interaction between PRKCI and SQSTM1, demonstrating that PRKCI upregulated SQSTM1 and mediated critical functions in the proliferation and progression of osteosarcoma cells through the activation of the Akt/mTOR signaling pathway.…”
Section: Discussionmentioning
confidence: 99%
“…Подобно опухолям взрослых, опухоли у детей поддерживают иммуносупрессивное микроокружение, включая инфильтрацию ассоциированными с опухолью макрофагами и клетками-супрессорами миелоидного происхождения, а также метаболические нарушения, которые создают микроокружение, враждебное пролиферации цитотоксических лимфоцитов [64]. В настоящее время не зарегистрировано ни одного лекарственного препарата CAR-T-терапии при мезенхимальных опухолях у детей, тем не менее, ведутся исследования, оценивающие возможность применения CAR-T-технологии в терапии остеосаркомы -наиболее распространенного злокачественного новообразования костей у детей и подростков [65,66].…”
Section: Car-т-клетки при солидных опухолях у детейunclassified